Selection of the Best Administrative Staff Using Elimination Et Choix Traduisant La Realite (ELECTRE) Method. Issue 1 (June 2021) - Sirait, Sarida; Saragih, Doris Yolanda; Sugara, Heru; Yunus, Muhammad; Sumaizar,; Hanafiah Ali, M.; Mulia Siregar, Victor Marudut; Indrawan, Isa; Anwar, Umar; Defliyanto, D
Abstract: The research was carried out aimed at solving problems in selecting the best administrative staff at the Vita Insani Hospital. This problem is overcome by designing a decision support system that is able to help decision makers to select the best administrative staff. This DSS was designed using the Elimination Et Choix Traduisant La Realite (ELECTRE) method. From the results of this study it is concluded that the Electre method is very appropriate to use as a decision support tool where the best alternative is the Vita_staff_001 administrative staff which eliminates other alternatives by having a value of 1 as much as 3 which is more than the value of 1 for the other alternatives.